Determining Timing of Births and Habitat Selection to Identify Lambing Period Habitat for Bighorn Sheep - Robinson, Rusty W.; Smith, Tom S.; Whiting, Jericho C.; Larsen, Randy T.; Shannon, Justin M. (Frontiers in Ecology and Evolution, 2020)
Timing of births in ungulates is influenced by ecological factors, and differences in seasonality of births have evolutionary implications for these mammals. Birthing habitat is one of the most important home-range attributes for ungulates, and disturbances during this time can decrease survival of young and population growth. We calculated timing of births and quantified habitat selected by nursery groups of desert bighorn sheep (Ovis canadensis nelsoni) to produce and project a GIS model of nursery habitat. We then applied that model to identify suitable nursery habitat in an adjacent area for a population of Rocky Mountain bighorn sheep (O. c. canadensis). We monitored 19 GPS-collared females from 2012 to 2013 to delineate the birthing season. We used GPS locations during that time and logistic regression within a model-selection framework to differentiate between nursery habitat and random locations based on habitat and anthropogenic covariates. We used model coefficients to produce and project a GIS model of nursery habitat. Across both years, 89% of 45 births occurred in May (range = April 27 to June 9). We quantified covariate values at 750 nursery and 750 random locations during that time. The top model included elevation, slope, terrain ruggedness, aspect, existing vegetation type, and distance to trails and roads. Those variables predicted nursery habitat for desert bighorn sheep (rho = 0.99, P = 0.02). We then overlaid that model on 1,130 GPS locations from 17 female Rocky Mountain bighorns. In both areas, an average of 71% of locations were in the top two (of five) probability categories (high and medium high). Females in nursery habitat preferred steep, north-facing slopes, rugged terrain, low elevation, and avoided roads. Our GIS model projected areas of nursery habitat for adjacent desert and Rocky Mountain bighorns and provided land managers with a map of nursery habitat in areas where resource extraction and recreation are increasing. Identifying timing of parturition, and high-probability nursery habitat, will help managers mitigate temporal and spatial conflicts between bighorn sheep and anthropogenic activities. Similar data regarding timing of births and a GIS model can be applied to conserve habitat for other ungulates as well.